La culture de la patate douce et du maïs chez les Krahô - Ana Gabriela Morim de Lima (Revue d'ethnoécologie)
From an anthropological perspective, this article proposes a reflection on human-plant interactions based on an ethnographic study of the complementary opposition between sweet potato and maize crops among the Krahô, an Amerindian people of Central Brazil. The indigenous knowledge regarding these plants is linked to notions of personhood, gender and kinship relations, the annual calendar, myth and ritual, as well as other forms of conceiving temporality and territoriality. Throughout the article, it will be explored the connections between the life cycles of gardens, villages, people and plants, highlighting the homology and interdependence between ecological, social and cosmological space-time. In the context of recent ethnological debate, Krahô’s ethnography offers original elements for thinking about other forms of human-plant interaction that, going beyond human exceptionalism, reveal a general effort to produce kinship ties with cultivated plants.